2017
DOI: 10.1186/s13064-017-0084-3
|View full text |Cite|
|
Sign up to set email alerts
|

Rp58 and p27kip1 coordinate cell cycle exit and neuronal migration within the embryonic mouse cerebral cortex

Abstract: BackgroundDuring the development of the mammalian cerebral cortex, newborn postmitotic projection neurons are born from local neural stem cells and must undergo radial migration so as to position themselves appropriately to form functional neural circuits. The zinc finger transcriptional repressor Rp58 (also known as Znf238 or Zbtb18) is critical for coordinating corticogenesis, but its underlying molecular mechanism remains to be better characterised.FindingsHere, we demonstrate that the co-expression of Rp58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Gene inactivation by a knockout approach has demonstrated that RP58 plays a crucial role in neuronal proliferation, migration, and differentiation in the developing cerebral cortex, as well as regulation of embryonic myogenesis . Further analyses showed that Id (inhibitor of differentiation) genes are direct targets of RP58 .…”
Section: Association Between Translin Monomers and The Transcriptionamentioning
confidence: 99%
See 1 more Smart Citation
“…Gene inactivation by a knockout approach has demonstrated that RP58 plays a crucial role in neuronal proliferation, migration, and differentiation in the developing cerebral cortex, as well as regulation of embryonic myogenesis . Further analyses showed that Id (inhibitor of differentiation) genes are direct targets of RP58 .…”
Section: Association Between Translin Monomers and The Transcriptionamentioning
confidence: 99%
“…Gene inactivation by a knockout approach has demonstrated that RP58 plays a crucial role in neuronal proliferation, migration, and differentiation in the developing cerebral cortex, as well as regulation of embryonic myogenesis. [48][49][50][51][52][53][54] Further analyses showed that Id (inhibitor of differentia-tion) genes are direct targets of RP58. 54,55 Protein structure analysis revealed that RP58 contains an extensively conserved region at the amino terminus, termed the BTB/POZ domain, and Kruppeltype zinc finger motifs in the carboxyl-terminal region.…”
Section: Association Between Translin Monomers and The Transcriptionamentioning
confidence: 99%
“…of its maximum area. Therefore, we calculated the fluorescence intensity in fluorescence units (FU) as (integrated fluorescent intensity/area) [14] for comparative measurements. Statistical analyses were carried out using Prism 6 (GraphPad, San Diego, CA, USA).…”
Section: Systematic Labelling Of All Cell Cycle Phases In Each Precurmentioning
confidence: 99%
“…FU-average intensity in fluorescence units. (E) Box plots showing p27 KIP1 levels by cell cycle phase for NSCs and IPCs (n = 185, 13,50,7,72,13,149,14). In plotting these graphs, we combine cells in G2 with the small percentage of cells (2% in NSCs and In proliferating cells, the relatively slow rate at which a FP-hCdt1 (30/120) protein matures means this marker is active at a weak level at the initiation of G1 phase, then increases as the cell proceeds through G1.…”
Section: Differential Organization Of Cell Cycle Phase-linked P27 Kipmentioning
confidence: 99%
“…After publication of the original article [ 1 ] it was realised that there were errors in figures 2a,b,f,g, which arose as a result of preparing figures from data collected and analysed at the same time as the work reported in [ 2 ] (Supplementary Figure 1 of [ 2 ]).…”
Section: Correctionmentioning
confidence: 99%